Sulfobetaine N‐Chloramines: Chemical Synthesis and Antibacterial Application. Issue 39 (21st October 2019) - Li, Lingdong; Wang, Hande; Jin, Yanan; Wang, Peiqi; Jia, Dongxue
Abstract: A series of sulfobetaine N ‐chloramines, covalently combining an N ‐chloramine unit and a sulfobetaine unit with varied intercharge linkers, were chemically synthesized. Preliminary antibacterial tests showed that the antibacterial activity decreased as the methylene linker increases from ‐(CH2 )2 ‐ to ‐(CH2 )8 ‐ except the linker of ‐(CH2 )6 ‐, which exerted remarkable bactericidal efficacy unusually. In addition, the analogue with the linker of ‐(CH2 )10 ‐ displayed the highest bactericidal efficacy among all synthetic N ‐chloramines, probably due to its neutral zwitterionic characteristic on structure. Our research provided highly efficacious antibacterial agents together with the vital references to design novel ionic N ‐chloramine biocides. Abstract : Chemical synthesis of sulfobetaine N ‐chloramines with varied intercharge linkers were achieved, and the structure‐bicocidal activity relationship were preliminarily investgated. The N ‐chloramine analog with linker of ‐(CH2 )10 ‐ displayed the highest antibacterial activity, probably due to its neutral zwitterionic characteristic structure and its unique disperse on bacteria cell suafce.